2019
DOI: 10.3390/cancers11121912
|View full text |Cite
|
Sign up to set email alerts
|

A 4-Year Retrospective Analysis of Salivary Gland Cytopathology Using the Milan System for Reporting Salivary Gland Cytology and Ancillary Studies

Abstract: The cytopathology of salivary glands presents major challenges due to the heterogeneity of benign and malignant neoplasms, which is reflected in the large range of WHO 2017 Classifications. Fine needle aspiration (FNA) of salivary gland tumours is still the favoured initial approach as it results in good sensitivity and specificity. The Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) was published in 2018 and comprises seven categories. We report results from a 4-year retrospective analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 20 publications
3
47
0
Order By: Relevance
“…The non‐diagnostic category carries a risk of malignancy (ROM) of 25%. The publication of papers analysing the role of the Milan System has further defined the ROM . In a recent study by Tommola et al, the non‐diagnostic category had a 0% ROM; however, a recent meta‐analytic study by Farahani analysed 92 studies including 16,456 SG‐FNA with surgical follow‐up The data from this study revealed a 7% ROM for the non‐diagnostic category based on 44 cases with histological follow‐up.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…The non‐diagnostic category carries a risk of malignancy (ROM) of 25%. The publication of papers analysing the role of the Milan System has further defined the ROM . In a recent study by Tommola et al, the non‐diagnostic category had a 0% ROM; however, a recent meta‐analytic study by Farahani analysed 92 studies including 16,456 SG‐FNA with surgical follow‐up The data from this study revealed a 7% ROM for the non‐diagnostic category based on 44 cases with histological follow‐up.…”
Section: Introductionmentioning
confidence: 92%
“…The series also supported the statement that the non‐diagnostic rate should be <10%. Nevertheless, the rate of non‐diagnostic FNA in the studies conducted at general hospitals was 21.28% ± 17.47% as compared to 4.38% ± 2.32% performed at referral or tertiary centres demonstrating an advantage for the latter group . The most common clinical management is represented by a repeat FNA with the use of ultrasound guidance and/or rapid on‐site evaluation in order to prevent a second non‐diagnostic result .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations